2017
DOI: 10.1002/anie.201611072
|View full text |Cite
|
Sign up to set email alerts
|

Removal of Multiple Contaminants from Water by Polyoxometalate Supported Ionic Liquid Phases (POM‐SILPs)

Abstract: The simultaneous removal of organic, inorganic, and microbial contaminants from water by one material offers significant advantages when fast, facile, and robust water purification is required. Herein, we present a supported ionic liquid phase (SILP) composite where each component targets a specific type of water contaminant: a polyoxometalate‐ionic liquid (POM‐IL) is immobilized on porous silica, giving the heterogeneous SILP. The water‐insoluble POM‐IL is composed of antimicrobial alkylammonium cations and l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
83
0
7

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 118 publications
(91 citation statements)
references
References 34 publications
1
83
0
7
Order By: Relevance
“…More recently, Streb and co‐workers have prepared POM‐ILs from lacunary Keggin derivatives including [SiW 11 O 39 ] 8− and [α‐PW 9 O 34 ] 9− and simple QAAs, predominantly tetrahexyl‐, tetraheptyl‐, tetraoctyl‐, and trihexyl(tetradecyl)‐ammonium cations . Their targeted applications included water filtration and treatment, and anticorrosive/antibacterial coatings for metals and building stone . In these applications, both components of the POM‐IL were engaged in the application.…”
Section: Supramolecular Pom‐cation Aggregation Leading To Soft Mattermentioning
confidence: 99%
“…More recently, Streb and co‐workers have prepared POM‐ILs from lacunary Keggin derivatives including [SiW 11 O 39 ] 8− and [α‐PW 9 O 34 ] 9− and simple QAAs, predominantly tetrahexyl‐, tetraheptyl‐, tetraoctyl‐, and trihexyl(tetradecyl)‐ammonium cations . Their targeted applications included water filtration and treatment, and anticorrosive/antibacterial coatings for metals and building stone . In these applications, both components of the POM‐IL were engaged in the application.…”
Section: Supramolecular Pom‐cation Aggregation Leading To Soft Mattermentioning
confidence: 99%
“…Vor kurzem zeigten Streb und Mitarbeiter, dass POM‐ILs auf Basis von lakunären Keggin‐Derivaten wie [SiW 11 O 39 ] 8− und [α‐PW 9 O 34 ] 9− sowie einfachen QAAs, insbesondere Tetrahexyl‐, Tetraheptyl‐, Tetraoctyl‐ und Trihexyl(tetradecyl)ammoniumkationen, zugänglich sind . Ihre Zielanwendungen umfassen Wasserfiltration und ‐reinigung sowie Korrosionsschutzbeschichtungen für Metalle und Werksteine . In diesen Anwendungen haben beide Komponenten der POM‐IL eine Funktion.…”
Section: Supramolekulare Pom‐kation‐aggregation Zur Bildung Weicher Munclassified
“…In the past, extensive studies have been reported to unravel the scopeo fs uch functional materials as activated porous carbon, [5] zeolites, [6] silica particles, [7][8][9][10][11][12][13] graphene oxide, [14,15] metals or metal oxides, [16,17] natural minerals [18][19][20] etc. as adsorbents for remediationo fm etal ions from water.T he search for new and efficient adsorbentsh as prompted the design and synthesis of functional polymers, [21][22][23][24][25][26][27] metal organic frameworks, [28][29][30] polymeric composites [31][32][33] and biohybrids.…”
Section: Introductionmentioning
confidence: 99%